Proceedings of the 4th International Conference of Fluid Flow, Heat and Mass Transfer (FFHMT'17) 2017
DOI: 10.11159/ffhmt17.108
|View full text |Cite
|
Sign up to set email alerts
|

Study and Numerical Analysis of Compressor Transition Duct

Abstract: -In the modern age of aviation, turbofan engines are designed with pressure ratio as high as 40 and by-pass ratios in excess of 8. Multi spool compressor connected with a transition duct fulfils the requirement of high pressure ratio. The inter-stage annular Sshaped transition duct connects the exit of LP compressor to the inlet of HP compressor. Due to the curvature of the duct, turbulence losses and flow separation losses will develop inside the duct. Sometimes, struts are placed inside the duct for better g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The loss coefficient increased from 0.040 to 0.042 for without compressor case whereas it increased from 0.035 to 0.038 with compressor case. Milanovic et al [43] Baloni et al [44] One, six and eight strut -Computational fluid dynamics showed the capability to capture the flow physics of the duct accurately under the strutted environment. -Similar to the experimental study, numerical simulation also captured wakes near to the trailing edge of the strut.…”
Section: Number Of Struts Remarkmentioning
confidence: 99%
“…The loss coefficient increased from 0.040 to 0.042 for without compressor case whereas it increased from 0.035 to 0.038 with compressor case. Milanovic et al [43] Baloni et al [44] One, six and eight strut -Computational fluid dynamics showed the capability to capture the flow physics of the duct accurately under the strutted environment. -Similar to the experimental study, numerical simulation also captured wakes near to the trailing edge of the strut.…”
Section: Number Of Struts Remarkmentioning
confidence: 99%